In chronic lymphocytic leukaemia with complex karyotype, major structural abnormalities identify a subset of patients with inferior outcome and distinct biological characteristics. (2nd April 2018) - Rigolin, Gian Matteo; Saccenti, Elena; Guardalben, Emanuele; Cavallari, Maurizio; Formigaro, Luca; Zagatti, Barbara; Visentin, Andrea; Mauro, Francesca R.; Lista, Enrico; Bassi, Cristian; Lupini, Laura; Quaglia, Francesca Maria; et al.
Summary: Complex karyotype (CK) is a negative prognostic factor in chronic lymphocytic leukaemia (CLL). However, CK is a heterogeneous cytogenetic category. Unbalanced rearrangements were present in 73·3% of 90 CLL patients with CK (i.e. ≥3 chromosome aberrations in the same clone), and were associated with a shorter overall survival ( P  =   0·025) and a shorter time to first treatment ( P  =   0·043) by multivariate analysis. Patients with unbalanced rearrangements presented a distinct mRNA expression profile. In conclusion, CLL patients with unbalanced rearrangements might represent a subset of very high‐risk CLL patients with distinct clinical and biological characteristics.